The Tissue Clock Network: Driver and Gatekeeper of Circadian Physiology: Circadian rhythms are integrated outputs of central and peripheral tissue clocks interacting in a complex manner – from drivers to gatekeepers. (1st March 2020) - Harder, Lisbeth; Oster, Henrik
Abstract: In mammals, a network of cellular circadian clocks organizes physiology and behavior along the 24‐h day cycle. The traditional hierarchical model of circadian clock organization with a central pacemaker and peripheral slave oscillators has recently been challenged by studies combining tissue‐specific mouse mutants with transcriptome analyses. First, a surprisingly small number of tissue rhythms are lost when only local clocks are ablated and, second, transcriptional circadian rhythms appear to be regulated by a complex mix of local and systemic factors. As reviewed here, these findings suggest a more integrated model of clock network interaction with the central pacemaker as the main source of behavioral and systemic–physiological rhythms and peripheral clocks controlling some local rhythms while at the same time acting as gatekeepers that temporally adjust cellular responses to external stimuli. Abstract : Integrated model of clock network interaction. The central clock in the suprachiasmatic nucleus (SCN) acts as the main source of behavioral and systemic–physiological rhythms (A) while peripheral clocks control some local rhythms (B) and at the same time act as gatekeepers that temporally adjust cellular responses to external stimuli (C).